EVALUATION OF THE LEVEL DAMAGE OF FLEXIBLE PAVEMENT ON THE SINGOSARI – RANDU AGUNG HIGHWAY MALANG REGENCY - Urviy, Urviy Sausan Listikhawa; Ratnaningsih, Dwi; Riyanto, Sugeng (Jurnal Online Skripsi Manajemen Rekayasa Konstruksi (JOS-MRK), 2023)
Singosari – Randu Agung Highway, Malang Regency, is a road as a national road and have a road functions as an arterial primary. This road segment is one of the roads that have a heavy volume of vehicles, due to excessive repetitive traffic loads (overloading), then resulting for damages surface layer and a decrease in the road quality. Based on that cased, this study have a purpose to evaluate the condition of road pavement and determine the value of road pavement conditions based on the Surface Distress Index (SDI) method and International Roughness Index (IRI) method which is used as a basis for determined alternative treatment that need to be done. Visual pavement condition assessment along 4 km was obtained by conducting field surveys with a form refers to Bina Marga Method (001-01/M/BM/2011). The result of the evaluation found that road damge such as holes, longitudinal crack, alligator crack, block crack, and transverse crack. Based on the road conditions that have been evalauted, obtained results with 63% in good condition along 2.5 km, 35% in medium condition along 1.4 km and 3% in light damage condition along 0.1 km. The type of the treatment for the routine road maintenance consist of patching holes and filler cracks.